A Domain Decomposition Based Spectral Collocation Method for Lane-Emden Equations. (21st June 2017) - Guo, Yuling; Huang, Jianguo
Abstract: A domain decomposition based spectral collocation method is proposed for numerically solving Lane-Emden equations, which are frequently encountered in mathematical physics and astrophysics. Compared with the existing methods, this method requires less computational cost and is particularly suitable for long-term computation. The related error estimates are also established, indicating the spectral accuracy of the method. The numerical performance and efficiency of the method are illustrated by several numerical experiments.